Kambing Perap Margo: Tasstiee Margo / Syahirah Suraya Omar and Mohamad Shafizal Shilan - Omar, Syahirah Suraya; Shilan, Mohamad Shafizal (2022)
Subject Principles of Entrepreneurship, ENT530 is about entrepreneurship which we have been students throughout this semester. We also learned about Copywriting strategy. So, while studying this subject and this sub topic, there is one task that we have to do to complete our final assignment which is Social Media Report. We had to find a product to sell and market on social media sites and we chose Facebook as our sales platform. We know that this Facebook platform is a large and easily accessible platform for the public and will be a useful platform for selling goods. For this task, we have chosen to sell frozen food which is marinated goat. The brand name of the product is Kambing Perap Margo. We chose this product is due to the relatively high demand and increasingly famous in the country, especially in the state of Terengganu. This Kambing Perap Margo is a roasted lamb marinated with various spices that will make this marinade even tastier. In addition, this meat also uses very high quality and healthy meat. What is special about our marinated lamb is that every purchase will get a special black pepper sauce that is spicy and sweet. There are two ways of copywriting that we use in selling our product, namely soft-sell and hard-sell. This method is the method we have learned in ENT530 and will be adapted in our sales strategy. Thus, our report also will use Facebook as our main platform to promote our products and business.